Mapping major trends in global research in marine and coastal tourism: a bibliometric analysis - Mohd Adam, Syamimi; Mohammad Afandi, Syamsul Herman; W. Mohamad, Wan Norhidayah; Hassan, Suziana (Penerbit UMT, 2022)
Recently, marine and coastal tourism have become a rapidly rising trend in the tourism sector. This paper aims to scrutinise the significant trends in global research on marine and coastal tourism using bibliometric analysis. The bibliographic data of 969 studies were examined from the Scopus database to identify marine and coastal tourism research activity and the period was defined from 1986 until 2020. The dataset was retrieved on 3 October 2020. All the datasets were gathered without regard to a specific historical line to include those publications connected to both phases of the search. The reason behind gathering all the information was because of its contribution to this field. The study will highlight the journal’s most prominent trends in terms of publications, universities, regions, keywords and journals. This study aids to provide a summary of the field of marine tourism. This study would help to increase ones understanding by exposing them to a major part of the primary research. The existing research points and possible future research topics will be documented in this study.